THE INVESTMENT POTENTIAL OF HOUSEHOLD: CONCEPT AND EVALUATION OF HOUSEHOLDS - Sydorchuk, Anatoliy; Kyrylenko, Olha (Socio-economic relations in the digital society, 2022)
The aim of the article is to study the investment potential of households. It was found that the vast majority of scientific papers on this issue reveal the concept of investment potential through the prism of the possible participation of households in their own savings in the financial market. It is proposed to formulate investment potential as the number of cash resources outside deposit-taking corporations that can be used by households to make investments - purchase risky financial instruments (stocks, cash, foreign currency deposits, precious metals) and provide higher income in the long run (over 20 years) for inflation. In contrast to existing approaches, this definition reflects the relationship between the concept and household investment and its expected outcome. To assess the investment potential, it is proposed to use the coefficient of the same name, which is determined by the method of dividing the volume of the monetary aggregate (measures cash outside deposit-taking corporations) by the total household income. It is noted that the higher the value of the ratio, the higher the level of investment potential and the more opportunities to ensure the financial stability of households in the long run. The analysis showed that despite the general growth of both household incomes and money supply in circulation outside deposit-taking corporations, the investment potential of domestic households for the period 2012–2020 no improve. This conclusion allows us to make the calculated value of the investment potential ratio is 2020, which is almost equivalent to 2012. The low level of financial literacy and psychological factors we identify as the main reasons influencing the state of investment potential of households and prospects for its implementation in practice.
Keywords: household; investment potential; risk; income; monetary aggregate; coefficient